Hungarian Monitoring, 22 June 1989 . [Magyar rádiófigyelő], 1989. június 22 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Belgian socialist party supports repatriation of Anna Kéthly's remains to Hungary - British press opinions on the Budapest roundtable discussions - GDR concerned at developments in Hungary - French newspapers full of Romanian Iron Curtain news - Hundreds of students demand Jaruzelski's resignation in Kraków - On internal contradictions within Polish Solidarity movement Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) accepts Opposition Roundtable request and will not recommend debate on proposed modifications to the constitution at next Tuesday's opening session of Parliament - More and more Hungarian Socialist Workers' Party (MSZMP) reform circles demand Károly Grósz's resignation - Leading judge at Imre Nagy trial Ferenc Vida is convinced that no charges would be brought against Nagy today Külpolitika: - A belga szocialista párt támogatja, hogy hozzák haza Magyarországra Kéthly Anna földi maradványait - Brit lapvélemények a budapesti kerekasztal tárgyalásokról - Az NDK-t aggodalommal tölti el magyarországi fejlemények - A francia lapok tele vannak a román vasfüggöny híreivel - Krakkóban több száz diák követelte Jaruzelski lemondását - A lengyel Szolidaritás belső ellentéteiről Belpolitika: - Az MSZMP elfogadta az Ellenzéki Kerekasztal kérését és nem fogja javasolni a Parlament jövő kedden kezdődő ülésszakán, hogy vitassák meg az alkotmány módosításáról szóló törvénytervezetet - Egyre másra sürgetik az MSZMP reformkörei Grósz K. leváltását - Vida Ferenc a Nagy Imre per vezető bírója meg van győződve arról, hogy ma semmilyen vádat nem emelnének Nagy Imre ellen